Differentiation of Diatom Guilds in Extreme Environments in the Andean Altiplano - Heine-Fuster, Inger; López-Allendes, Camila; Aránguiz-Acuña, Adriana; Véliz, David (Frontiers in Environmental Science, 2021)
The Andean Altiplano is characterized by its isolation, high altitude (> 3,600 m.a.s.l.), and a unique biodiversity, contains water systems such as lakes, rivers, wetlands, and salt flats. Near the southernmost area of the Andean Altiplano are two salt flats, Carcote and Ascotán, the former almost undisturbed by human intervention, and the latter historically intervened by brine-mining. These mining activities deplete, pollute, and alter waterflow, suggesting a significant threat to ecosystem functions. To identify the main factors promoting biotic community differentiation in these salt flats under different levels of human intervention, the aim of this study was to compare diatom community indices by guilds (high-profile, low-profile, and motile) between these systems, with a functional perspective, their relationship to environmental conditions, and the potential anthropic impact on their community structures. Diatom guilds were compared between salt flats based on their diversity, species richness, and abundance relative to ionic concentrations and granulometry. Beta diversity and the percentages of nestedness and turnover for each guild were also estimated. Results showed significant differences in ecological variables between the two salt flats. The largest values of species abundance, richness, and diatom diversity were measured in Carcote, suggesting greater primary productivity and diversity. The results also showed that the species composition of the motile guild was more differentiated between salt flats than other guilds (with the greatest diversity and richness), suggesting that motile diatoms are a key guild in maintaining the diatom community and that species from this guild are more sensitive to local conditions from each salt flat. Additionally, beta diversity by all guilds was mainly explained by turnover rather than nestedness, and the turn-over was highest for motile and low profile. A more heterogeneous community was observed in Ascotán, showing that the mechanisms of diversity maintenance, such as dispersion abilities, were salt flat-dependent. This suggests that the highest diversity could be related to human use, which challenges us to reexamine the effectiveness of past conservation activities in the area and to develop future strategies including both connected basins.